Development and experimental validation of numerical formulations of a heuristic model in WEDM of H13 tool steel. (16th September 2021) - Singh, Meinam Annebushan; Das, Koushik; Sarma, Deba Kumar
Proper identification of the effect of various process parameters in wire-electrical discharge machining process is a very important area that needs a thorough analysis. Also, advancement in technology has considerably limited the user interface. The knowledge of the interdependence of these parameters will prove to be an important criterion to further enhance the machining technique. The present work focuses on the thorough analysis of the effect of the interdependence of process parameters in the machining of H13 tool steel. Experiments are performed to obtain the material removal rate for different operating conditions. A finite element-based backtrack numerical solver is developed to simulate the working voltage with the experimental results. The analyses show the interdependence of voltage, current, pulse on and off-time. A power allometric-based heuristic model is formulated to identify the interdependence of various process parameters. The proposed heuristic model has been validated with the experimental results, performed at random parametric conditions.